Real-world evidence in gynecologic cancers presented at key oncology conferences in the United States: Distribution and factors related to high-tier acceptance - Elizabeth A. Szamreta; Mansi Modi; Ramu Periyasamy; Bhavani Yamsani; Pattabhi Machiraju; Neetu Menghani; Matthew Monberg (PLoS ONE, 2025)
Purpose To describe the distribution, trends, and characteristics of types of real-world evidence (RWE) abstracts presented at key oncology congresses. Methods Data on gynecologic cancers (cervical, ovarian, endometrial, and multiple gynecologic/other) were extracted from the American Society of Clinical Oncology (ASCO) and the Society of Gynecologic Oncology (SGO) conference databases (2018–2020) to: a) identify the proportion of clinical trial (CT) versus RWE abstracts accepted; b) describe the distribution and tier of acceptance of RWE versus CTs; c) analyze the characteristics (authorship, data source, data type, study design, outcome[s], and presence of statistically significant results) associated with RWE acceptance. Results Of 3163 abstracts screened, 2271 (77% RWE, 23% CTs) were included. RWE represented a higher proportion of work at SGO versus ASCO (70% vs 30%). Overall, more RWE studies versus CTs were accepted as posters (75% vs 60%), while fewer were accepted as oral presentations (4% vs 20%; p < 0.001 for both). Among RWE abstracts, 90% had academic author(s), 68% of studies were from North America, 45% used other clinical data sources, and nearly 32% reported statistically significant results. Approximately 60% of RWE were retrospective and 9% were prospective. The most common outcomes in RWE abstracts were molecular analyses (18%) and survival based on treatment efficacy (13%; p < 0.001). Conclusion RWE abstracts were accepted for presentation more frequently at SGO versus ASCO, and majority of them were presented as posters. While RWE abstracts are prevalent and provide valuable data for healthcare decision-making, they do not always achieve the visibility of CTs.